2022
DOI: 10.1039/d1np00051a
|View full text |Cite
|
Sign up to set email alerts
|

How different are marine microbial natural products compared to their terrestrial counterparts?

Abstract: Cheminformatics analysis shows that most marine microbial natural products are like terrestrial microbial natural products. New methods to access novel marine microbial chemistry are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 94 publications
(97 reference statements)
1
40
0
Order By: Relevance
“…Actinomycete sources alone account for approximately 80% of novel antibiotics derived from the marine environment [178]. Studies targeting specific and understudied marine microbial phyla can result in a greater likelihood of finding specific marine compounds, since most compounds isolated from marine microorganisms are closely related to compounds isolated from terrestrial microorganisms [221]. Unfortunately, the marine environment is one of the most under-explored environments, but still holds as a promising source of new and innovative natural products [220], which is clearly illustrated in Figure 4.…”
Section: Marine Streptomyces As a Source Of Antibioticsmentioning
confidence: 99%
“…Actinomycete sources alone account for approximately 80% of novel antibiotics derived from the marine environment [178]. Studies targeting specific and understudied marine microbial phyla can result in a greater likelihood of finding specific marine compounds, since most compounds isolated from marine microorganisms are closely related to compounds isolated from terrestrial microorganisms [221]. Unfortunately, the marine environment is one of the most under-explored environments, but still holds as a promising source of new and innovative natural products [220], which is clearly illustrated in Figure 4.…”
Section: Marine Streptomyces As a Source Of Antibioticsmentioning
confidence: 99%
“…An interesting recent review by Voser et al [63] on "How different are marine microbial natural products compared to their terrestrial counterparts?" did an excellent job of summarizing 55,817 compounds reported from marine and terrestrial microorganisms and showed that 76.7% of the compounds isolated from marine microorganisms are closely related to compounds isolated from terrestrial microorganisms.…”
Section: Marine Actinomycetes: a Potential Frontier Of Bioactive Comp...mentioning
confidence: 99%
“…Interestingly, Voser et al, in their recent review using fingerprint cluster analysis, based on the MarineLit database, which covers compounds isolated from the marine environment between 1956 and 2020, and the NPAtlas database, which contains compounds isolated from microorganisms and published between 1877 and 2020, have found that marine fungal natural products (NPs) are nested with terrestrial fungal NPs at a relatively high proportion (74.6%). This indicates that marine and terrestrial fungi are more likely to share common biosynthetic gene clusters, or that marine sources of fungi are likely to be terrestrial “wash-ins” [ 65 ]. The authors have also found that most studies used potato dextrose or rice in sea water or sea salt as culture media for most of the marine-derived fungi.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%